Rede de tecnologia 5G: como medir os impactos sociais e econômicos na sociedade de Manaus com a chegada dessa tecnologia - Brito, Valéria de Jesus Souza (Brasil, 2024)
5G wireless technology has been bringing a wide range of possibilities that only a high-speed network is capable of providing, a hundred times more than its 4G predecessor, in addition to the high quality of signal transmission, low connection latency, greater number of connected devices and a more stable connection that will make it possible to instantly access information that the user intends to download, access services and content on the most varied topics. Faced with this frenzy, the State of Amazonas is in the implementation phase of 5G technology, initially in the capital (Manaus) of Amazonas, where local operators have been adapting and adapting their services, but after all, within this context, we will address this research work , the benefits that technology has been bringing to our Amazonian reality. Remembering that there is great difficulty for the telecommunications area in an environment in which population clusters are in areas geographically far from the network management headquarters, where the main means of transport is the river and also the constant bad weather that plagues this huge world green. The methodology we will use will be a bibliographical and exploratory research, in order to discover the main benefits that the emerging technology will bring and how it will change the lives of our Amazonian population. The results obtained indicate that adherence and use of the network brings material contributions in the scenario of the city of Manaus, but that specific studies are necessary in the city, as the works collected point to the scenario of other cities or regions, based on this observation, in the city of Manaus may also show similar results.